Engineering pervasive services for legacy software - Gordillo, Silvia Ethel; Rossi, Gustavo Héctor; Fortier, Andrés (2006)
In this paper we present a novel architectural approach to engineer applications that provide location-aware services; in particular, we explain how to extend existing software systems with location-aware services. We show how a clear separation of design concerns (e.g. applicative, context-specific, etc) helps to improve modularity. We stress that, by using dependency mechanisms among outstanding components, we can get rid of explicit rule-based expressions thus simplifying evolution and maintenance. We first motivate our research with a simple example. Next, we present the big picture of our architectural approach. Then we detail how to specify location-aware services; we present details of the services’ activation mechanisms. We finally we discuss some related work in the field. We conclude with some further issues in which we are now working.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 25 nov. 2008)
Proceedings of the International Workshop on Software Engineering for Pervasive Services, 2006, June.
Keywords: ARQUITECTURA DE SOFTWARE; INTELIGENCIA AMBIENTAL; SERVICIOS BASADOS EN LOCALIZACIÓN; APLICACIONES SENSIBLES AL CONTEXTO